Pharmacological profiles of recombinant and native insect nicotinic acetylcholine receptors. - Tomizawa, M.; Millar, N.S.; Casida, J.E. (Insect Biochemistry and Molecular Biology, 2005)
Nicotinic acetylcholine receptors (nAChRs) are targets for insect-selective neonicotinoid insecticides exemplified by imidacloprid (IMI) and mammalian-selective nicotinoids including nicotine and epibatidine (EPI). Despite their importance, insect nAChRs are poorly understood compared with their vertebrate counterparts. This study characterizes the [(3)H]IMI, [(3)H]EPI, and [(3)H]alpha-bungarotoxin (alpha-BGT) binding sites in hybrid nAChRs consisting of Drosophila melanogaster (fruit fly) or Myzus persicae (peach-potato aphid) alpha2 coassembled with rat beta2 subunits (Dalpha2/Rbeta2 and Mpalpha2/Rbeta2) and compares them with native insect and vertebrate alpha4beta2nAChRs. [(3)H]IMI and [(3)H]EPI bind to Dalpha2/Rbeta2 and Mpalpha2/Rbeta2 hybrids but [(3)H]alpha-BGT does not. In native Drosophila receptors, [(3)H]EPI has a single high-affinity binding site that is independent from that for [(3)H]IMI and, interestingly, overlaps the [(3)H]alpha-BGT site. In the Mpalpha2/Rbeta2 hybrid, [(3)H]IMI and [(3)H]EPI bind to the same site and have similar pharmacological profiles. On considering both neonicotinoids and nicotinoids, the Dalpha2/Rbeta2 and Mpalpha2/Rbeta2 receptors display intermediate pharmacological profiles between those of native insect and vertebrate alpha4beta2 receptors, limiting the use of these hybrid receptors for predictive toxicology. These findings are consistent with the agonist binding site being located at the nAChR subunit interface and indicate that both alpha and beta subunits influence the pharmacological properties of insect nAChRs.